PEMBUATAN DAN IMPLEMENTASI WEBSITE PROFIL SEKOLAH SEBAGAI MEDIA INFORMASI DAN PROMOSI DIGITAL SDN GENTENG KOTA BOGOR - Adi Cahyono; Ahmad Ramadhan; Afrian Endriartono; Aldi Yansah; Argo Satrio B.P.A; Alfito Dhonan; Aufa Zahir F.A; M. Farid Abdullah; Rafli Ilham; Sandi Pratama (Abdi Jurnal Publikasi, 2025)
The rapid development of information technology demands educational institutions to adapt to digital transformation, particularly in the dissemination of school information and promotion. SD Negeri Genteng, Bogor City, previously relied on conventional media, such as bulletin boards and verbal communication or forms, which resulted in limited information reach. This Community Service (PKM) activity aims to create and implement a school profile website as a digital information and promotional medium for SD Negeri Genteng, Bogor City. The activity was conducted on Wednesday, November 12, 2025, offline using an interactive method that involved teachers and administrative staff as partners. The implementation methods included needs analysis, website development, system implementation, and training on website content management. The results of this activity show that the school profile website was successfully developed and is capable of displaying essential information such as the school's profile, activities, achievements, facilities, and registration information. Furthermore, the training activity significantly improved the participants' understanding and skills in managing the website independently. This PKM activity not only produced a website but also provided a positive impact in the form of increased capacity of the school's human resources in utilizing information technology. The existence of the website is expected to make information dissemination more effective and support the school's digitalization process sustainably.